2018
DOI: 10.1111/nyas.13996
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mindfulness meditation on sleep quality: a systematic review and meta‐analysis of randomized controlled trials

Abstract: There is a growing interest in the effectiveness of mindfulness meditation for sleep disturbed populations. Our study sought to evaluate the effect of mindfulness meditation interventions on sleep quality. To assess for relative efficacy, comparator groups were restricted to specific active controls (such as evidenced‐based sleep treatments) and nonspecific active controls (such as time/attention‐matched interventions to control for placebo effects), which were analyzed separately. From 3303 total records, 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
172
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(191 citation statements)
references
References 68 publications
(125 reference statements)
12
172
1
6
Order By: Relevance
“…These results are consistent with many past findings indicating that mindfulness-based interventions improve subjective sleep quality (Rusch et al, 2019). While some evidence suggests mindfulness training can improve objective sleep parameters in populations with sleep problems such as insomniacs and cancer patients and survivors (Gross et al, 2011;Garland et al, 2014;Lengacher et al, 2015), effects have rarely been observed in non-clinical populations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with many past findings indicating that mindfulness-based interventions improve subjective sleep quality (Rusch et al, 2019). While some evidence suggests mindfulness training can improve objective sleep parameters in populations with sleep problems such as insomniacs and cancer patients and survivors (Gross et al, 2011;Garland et al, 2014;Lengacher et al, 2015), effects have rarely been observed in non-clinical populations.…”
Section: Discussionsupporting
confidence: 92%
“…Both mental health symptoms and sleep problems are prevalent in elite athletes, and the National Collegiate Athletic Association as well as the International Olympic Committee have emphasized the need for improved sleep to benefit health and performance in this population (Kroshus et al, 2019;Reardon et al, 2019). Mindfulness-based stress reduction (MBSR) is a cognitive training program that can improve psychological well-being and sleep quality (Kabat-Zinn, 1982;Grossman et al, 2004;Cincotta et al, 2011;Li et al, 2018;Rusch et al, 2019), and thus may indirectly benefit athletic performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It had moderate strength of evidence showing improved sleep quality at post-intervention and follow-up in the former (ES = .33 and .54, respectively). There was low effect on sleep quality at post-intervention and follow-up in the latter (ES = .03 and −.14, respectively) [25]. As this current study lacked a control group, it is recommended to incorporate either specific or nonspecific active controls in future studies.…”
Section: Discussionmentioning
confidence: 89%
“…DOI: http://dx.doi.org/10.17352/apt.000010 anxiety or stress [22,23]. However, although meditation has also been demonstrated to improve insomnia [24], it does not seem to signifi cantly and categorically increase the quality of sleep [25].…”
mentioning
confidence: 99%